THE COLLECTIVE INTELLIGENCE IN THE COLLECTIVE SPORT (Fiep Bulletin - online, 2011)
Science, today, has discovered almost every minute, the information change in a very quick process, and must be attentive to changes and processes. It is understood that the reason led us to arrive at this stage, this current level was the core of practical techniques, empirical facts and its laws, which make up the element of continuity, which was being improved and expanded over the history of mankind. To investigate the collective intelligence and its contribution to collective sports, especially in the basketball which is the focus of this work, especially when the time allowed to basketball player in mobilizing his actions both defensive and offensive is in the context of situations, which are the real situations of the game. Basketball is a game of speed, and appear each time occurrences that lead players to think quickly, and there are also changes and frequent changes of attack and defense, forcing the athlete to change the situation quickly. For Lévy (2007), the rate of technology change on an almost daily basis are causing transformation in the world in humans and therefore the technique is now one of the most important to work in the epistemological field. Drawing a parallel technique, stated by Lévy, that can reach all dimensions, then it also believes that through it, you can achieve perfection in a game, therefore, come to win the basketball game, because the game has two spaces, the defenders and the attackers, while a common ground for players that move on it: the court.
Keywords: Collective intelligence; basketball; technique